Innovation Complementarity and Environmental Productivity Effects: Reality or Delusion? Evidence from the EU - Marianna Gilli; Susanna Mancinelli; Massimiliano Mazzanti (Fondazione Eni Enrico Mattei (FEEM), 2013)
Innovation is a key element behind the achievement of desired environmental and economic performances. Regarding CO2, mitigation strategies would require cuts in emissions of around 80-90% with respect to 1990. We investigate whether complementarity, namely integration, between the adoption of environmental innovation measures and other technological and organizational innovations is a factor that has supported reduction in CO2 emissions per value added, that is environmental productivity. We merge new EU CIS and WIOD meso level data to assess the innovation effects on sector CO2 performances at a wide EU level. We find that jointly adopting different innovations is not a significant factor to increase environmental productivity, neither for the entire economy nor for manufacturing or narrower ETS sectors. The only case where a complementarity arises is for Northern EU manufacturing sectors that integrate eco innovations with product and process innovations to support environmental productivity. We believe that the lack of integrated innovation adoption behind environmental productivity performance is a signal of the current weaknesses economies face in tackling climate change and green economy challenges. Incremental rather than more radical strategies have predominated so far; this is probably insufficient when we look at long-term economic and environmental goals.
Keywords: O; Q; 330; Complementarity; Innovation; Climate Change; Sector Performance